Harvendusraietel toimunud metsaõigusnormide rikkumise juhtumite hindamine - Korjus Henn; Mets Mihkel; Kangur Ahto (Metsanduslikud Uurimused, 2021)
Three cases of violation of forest management regulations in Estonia in 2004, 2005 and 2007 are presented in the study where the required lower limit of basal area after thinnings was not followed. These stands were revisited in 2017 to assess the impacts of such thinnings. The actual thinnings were well justified from the silvicultural and economic viewpoints. All three stands were ecologically in good condition in 2017. Also, all three stands had already reached the required age or dimensions allowing regeneration cutting in 2017. Forest management regulations on thinning did not work well in the studied cases and therefore some changes in the current regulations are necessary in Estonia.